Rice protein concentrate is a well-accepted, highly digestible protein source for adult cats - Morris, Elizabeth; Perumalla, Sunil; Stiers, Cheryl; Gross, Kathy (Frontiers in Veterinary Science, 2023)
The use of rice protein concentrate (RPC) as a protein source in cat food is uncommon. Therefore, this study aimed to determine the acceptability and digestibility of foods formulated to contain increasing levels of RPC to support its inclusion in foods for adult (non-gravid, non-lactating) cats. Increasing levels of RPC (0, 7, 14, and 28%) were formulated into test foods fed to 24 cats in a Latin square design with 15-day periods and no washout between periods. Food intake and fecal scores were measured to determine the acceptability of test foods. Fecal output was measured on days 11–15. Food and fecal samples from day 15 of each period were analyzed for nutrient composition to calculate the macronutrient digestibility of the test foods. Analysis of variance and orthogonal contrasts were used to assess the effects of RPC inclusion on food intake, fecal output, fecal scores, and macronutrient digestibility. The results showed that as-fed (AF), dry matter (DM), and gross energy (GE) intake increased with increasing RPC levels (P > 0.05). Fecal output, both as-is and DM, was unaffected by RPC inclusion (P > 0.05); however, fecal scores increased linearly with increasing RPC inclusion (P < 0.001). Furthermore, true protein and apparent DM, GE, and carbohydrate (NFE) digestibility increased linearly with RPC inclusion (P < 0.05). Apparent fat digestibility was high for all test foods but was unaffected by RPC inclusion (P = 0.690). Overall, the inclusion of RPC was well-accepted, improved fecal characteristics, and increased the apparent and true macronutrient digestibility compared to the control. Therefore, this study demonstrated that RPC can serve as a high-quality and acceptable protein source for adult cats.